Quantifying the Effect of Grilling and Roasting on the Eating Quality of Lamb Leg Muscles - Hussein Al-Moadhen; Jarrod C. Lees; Liselotte Pannier; Peter McGilchrist (Foods, 2023)
Lamb eating quality was measured using untrained consumer sensory panels to determine the difference in intrinsic eating quality scores of grilled and roasted leg cut muscles. The Knuckle, Outside flat, and Topside from both legs of 65 mixed-sex lambs from diverse genetic backgrounds were prepared using alternative grill and roast cook methods. Each sample was eaten by 10 consumers and scored for tenderness, juiciness, flavor, and overall liking. All cuts scored higher (p < 0.001) when grilled compared with when roasted for all traits except for Topside tenderness. Grilled Knuckle scored higher than roast Knuckle by 13.6%, 23.9%, 14.4% and 15.8% for tenderness, juiciness, flavor, and overall liking, respectively. The grilled Outside flat scored higher than roast Outside flat by 14.1%, 27.1%, 10.9%, and 14.3% for tenderness, juiciness, flavor, and overall liking, respectively. Finally, grilled Topside scored higher than roast Topside by 21.3%, 7.4%, and 6.6% for juiciness, flavor, and overall liking, respectively. Carcass traits for intramuscular fat and shear force had a significant (p < 0.001) effect on all eating quality traits for both grill and roast cuts. Girth rib fat had a significant effect (p = 0.01) on tenderness and juiciness (p = 0.03) for Outside flat and Topside but had no effect (p > 0.05) on Knuckle for both grill and roast. This study identified that specific cooking methods can improve sensory traits for individual cuts and suggests that a cut-by-cook method eating quality model for sheepmeat can therefore increase consumer satisfaction.